20 Long-term survival outcomes of intravenous vs intraperitoneal chemotherapy in the treatment of advanced ovarian cancer. (13th November 2020) - Kim, R; Maganti, M; Bernardini, M; Laframboise, S; Ferguson, S; May, T
Abstract : Objectives: The role of intraperitoneal (IP) chemotherapy in the management of advanced ovarian cancer has been controversial. We aimed to compare survival outcomes associated with IP vs intravenous (IV) chemotherapy. Methods: We reviewed the long-term survival records of 271 women with stage IIIC or IV high-grade serous ovarian cancer treated with primary cytoreductive surgery (PCS) followed by IP or intravenous (IV) chemotherapy between 2001–2015 with a minimum follow-up of 4 years. 5-year progression free (PFS) and overall survival (OS) rates were compared using Kaplan-Meier survival analysis and covariates were evaluated using Cox regression analysis. Results: Women who received IP chemotherapy after PCS (n=91) were more likely to have undergone aggressive surgery (p<0.001), longer surgery (p<0.001), and had no residual disease (p<0.001) compared to the IV arm (n=180). Median follow-up was 51.6 months. Five-year PFS was 19% vs. 18% (p=0.63) and OS was 73% vs. 44% (p=0.00016) in the IP vs. IV arms, respectively. After controlling for covariates in a multivariable model, the use of IP was no longer a significant predictor of OS in the entire cohort (p=0.12). In patients with 0 mm residual disease, PFS was 28% vs. 26% (p=0.67) and OS was 81% vs. 60% (p=0.059) in IP (n=61) vs. IV (n=69), respectively. In patients with residual of 1–9 mm, PFS was 30% vs. 48% (p=0.076) and OS was 60% vs. 43% (p=0.74) in IP (n=29) vs. IV (n=31), respectively. Conclusions: IP chemotherapy showed a trend towards improved survival over conventional IV chemotherapy, especially in patients with no residual disease.